The Power of Visual Communication: Analyzing Visual Multimodal Cybertext Contexts in Indonesian Cyber Pragmatics - Rahardi, R. Kunjana; Rahmat, Wahyudi; Setyaningsih, Yuliana; Handoko, Handoko (Jurnal Arbitrer, 2025)
The rapid advancement of technology has significantly influenced the field of linguistics, particularly pragmatics, by expanding its scope from traditional intra-linguistic factors to encompass extralinguistic contexts such as social, cultural, situational, and cyber dimensions. This shift has ushered in functionalistic and post-functionalistic approaches in Indonesia, broadening the field to include semantic, cultural, cognitive, and cyber pragmatics. This study investigates how visual multimodal cybertext contexts in Indonesian digital media affect the interpretation of speech intent. This research draws on five selected visual, multimodal text excerpts from social media collected through free-flowing listening and note-taking, and it employs distributional and extralinguistic analysis methods. The findings reveal three primary roles of visual elements in cybertext: (1) typographic visuals that clarify background context for intended meaning, (2) visual icons that aid in contextual explanation, and (3) illustrative visuals that enhance understanding of the communicated message. These visual components are essential in facilitating accurate interpretation and engagement with speech acts in digital spaces. Addressing the gaps in understanding these elements can enhance communication strategies in Indonesian digital media, supporting clearer interaction and comprehension in a multicultural digital environment. This research contributes to the evolving field of cyber pragmatics by demonstrating the need for effective multimodal approaches to digital communication, especially in diverse sociocultural settings.